Bicontinuous network composite aerogel with large length-diameter ratio shell-core structure in-situ embedded porous silicon carbide foam and preparation method of bicontinuous network composite aerogel

By designing a large-length-diameter-ratio-core structure in a dual continuous network composite aerogel with porous silicon carbide foam embedded in nanowires, the problem of insufficient performance of nanowires embedded in nanowires in high temperature environments is solved, and the coordinated optimization of multifunctionality, energy absorption and high temperature resistance characteristics is achieved.

CN119608053AActive Publication Date: 2025-03-14ANHUI UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202510015388.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-14
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing nanowire embedded carbon foam materials have insufficient water oxygen resistance, poor seismic resistance, inability to take into account both rigidity and toughness, and the need to improve thermal insulation and multifunctional characteristics, which limit their application in high-temperature and harsh environments.

Method used

A dual continuous network composite aerogel with a large length-to-diameter ratio in situ embedded porous silicon carbide foam in the in-situ structure is designed by designing the continuous network structure of the silicon carbide nanowires in the putaway structure and the porous silicon carbide foam structure with a continuous network structure, forming a chemical bond with strong binding effect to achieve earthquake resistance and energy absorption effects.

Benefits of technology

It has significant advantages in the regulation of sound waves, electromagnetic waves, and light waves, as well as high-temperature oxidation and vibration resistance, achieving coordinated optimization of versatility, energy absorption and high-temperature resistance characteristics, and improving the comprehensive function and reliability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608053A_ABST
    Figure CN119608053A_ABST
Patent Text Reader

Abstract

Belonging to the technical field of high temperature resistant composite aerogel, the invention provides a bicontinuous network composite aerogel with large length-diameter ratio shell-core structure in-situ embedded porous silicon carbide foam, which comprises a shell-core structure and a skeleton, the shell-core structure comprises an inner core and a shell layer, the shell layer is of a ceramic silicone rubber layer structure, and the inner core is a SiC nanowire of a continuous network structure; the framework is porous silicon carbide foam with a continuous network structure; wherein the core-shell structure is embedded on the skeleton structure in situ to form an interspersed bicontinuous network composite structure. The invention also provides a preparation method, according to the method, by precisely designing the mechanical distribution of the nanowires, the ceramic skeleton and the porous structure on the coupling characteristic, the multifunctionality, energy absorption and high temperature resistance of the composite aerogel are synergistically optimized, and the composite aerogel has remarkable advantages in the aspects of regulation and control of sound waves, electromagnetic waves and light waves, high-temperature oxidation resistance and vibration resistance. Therefore, the composite material has wide application potential in the fields of aerospace, military protection, electronic equipment, building shock insulation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high temperature resistant composite aerogels, and in particular relates to a bicontinuous network composite aerogel with a large aspect ratio core-shell structure in-situ embedded with porous silicon carbide foam, and a preparation method thereof. Background Art

[0002] With the increasing demand for high-performance fireproof and heat-insulating materials in modern industry, existing inorganic composite aerogel materials are widely used due to their excellent high temperature resistance and heat insulation performance. However, the preparation of traditional inorganic composite aerogels mostly adopts a simple blending mode of zero-dimensional-one-dimensional, one-dimensional-one-dimensional, and two-dimensional-one-dimensional nanostructures for compounding. While obtaining high performance and multi-functions, a large number of weakly bonded structures are inevitably formed inside the material, which makes its performance decay aggravated in a long-term vibration service environment and its service life is not high. In addition, with the increase in energy demand, how to integrate high performance, multi-function, high strength, high toughness and other goals into a single structure has become one of the important demands in the field of lightweight composite structures. Therefore, the development of lightweight composite aerogels in the field of high temperature resistant heat insulation is of great significance. At present, in the design scheme of high-strength, high-flexibility and multifunctional structures in the field of high temperature resistance, the use of ceramic silicone rubber and inorganic template composite is one of the important technical solutions. However, the existing ceramic silicone rubber composite materials still face problems such as thermal expansion mismatch, weak interface bonding and easy oxidation. Therefore, reinforcement phases such as carbon foam and SiC nanowires are introduced into the design of ceramicizable silicone rubber composites to improve their comprehensive properties.

[0003] The Chinese patent with application number CN202411019183.1 discloses a ceramic silicone rubber composite tape. The invention has developed a ceramic silicone rubber composite tape, and further developed and synthesized a new type of organic-inorganic hybrid flame retardant, so that the product can ensure excellent mechanical properties while further improving the flame retardant properties and porcelain-forming properties. The product is wrapped around the copper busbar of the high-voltage connector in the battery pack of new energy vehicles, which plays a role in fire prevention and insulation. The Chinese patent with application number CN202311535978.3 discloses a high-efficiency fireproof silicone rubber composite sleeve and its preparation method, which can solve the problems that the existing silicone rubber sleeve cannot withstand long-term high-temperature impact above 1600°C, the bonding strength of silicone rubber and high-temperature resistant fiber tube is significantly reduced before and after high-temperature flame attack, the sleeve structure is severely damaged, and the preparation process uses a dip coating process to dilute the solvent to cause environmental pollution. The invention combines ceramic silicone rubber with high-silica fiber tubes, giving the material higher fire resistance while also having good mechanical properties and water resistance, aging resistance, and low temperature resistance. The Chinese patent application number CN202111180454.8 discloses a method for preparing a ceramic silicone rubber composite material. The ceramic silicone rubber composite material of the invention has good dimensional stability and mechanical properties under high temperature conditions; the ablation product can support a load of twice its own weight at 500-1000°C, has excellent residual strength at room temperature, and a bending strength of ≥2.69MPa; it has excellent electrical insulation properties at all temperatures, and the volume resistivity after ablation at 500-1000°C is ≥8.7×1011Ω·cm. The Chinese patent application number CN109734478A discloses a carbon foam resin-based composite substrate coated with a silicon carbide coating and a preparation method thereof. The invention uses carbon foam coated with a silicon carbide coating as a reinforcing phase to improve the high temperature resistance and compressive resistance of the composite substrate, and improves the overall dielectric properties of the composite substrate by filling the resin.

[0004] In terms of basic research, Chen Zhaofeng, Zhang Junxiong, Li Binbin and others deposited SiC nanowires on the three-dimensional skeleton of lightweight foam carbon composites based on chemical vapor infiltration technology, and did a lot of research on SiC nanowire / lightweight foam carbon composites (SnwLCF). The results show that silicon carbide nanowires divide the large pores of LCF and form many smaller pores inside it. The division of pores is the key to improving the thermal insulation performance of LCF; in addition, the content of SiC nanowires also has an important influence on the compression and thermal properties of SnwLCF (Journal of Alloys and Compounds, 2020, 829: 154609; Journal of Materials Science, 2020, 55: 4170-4178; Rare Metals, 2023, 42 (10): 3354-3363). Wang Yang and others successfully synthesized ultra-light and high-strength SiCnw@SiC foam materials with efficient microwave absorption and thermal insulation properties by using template sacrificial method and chemical vapor deposition method. Its microstructure is a new double-network structure formed by coupling morphology-controllable SiCnw with SiC skeleton. The introduction of SiCnw can not only provide more interface polarization and dielectric loss for SiC foam, greatly enhancing the microwave absorption capacity of composite foam, but also make it act as an excellent radiation absorber, which can effectively reduce the thermal conductivity of foam (ACS Applied Materials & Interfaces, 2021, 13 (18): 22017-22030).

[0005] However, existing nanowire-embedded carbon foam materials still have problems such as insufficient tolerance to high-temperature water and oxygen, poor seismic resistance, the inability to balance rigidity and toughness, and the need to improve thermal insulation and multifunctional properties. These problems limit their application in high-temperature and harsh environments. There is an urgent need to further optimize the structure and performance of the material to enhance its comprehensive functionality and reliability. Summary of the invention

[0006] Technical solution: In order to solve the above technical problems, the present invention provides a bicontinuous network composite aerogel with a large aspect ratio core-shell structure in-situ embedded with porous silicon carbide foam, specifically comprising: a core-shell structure, a skeleton;

[0007] The core-shell structure comprises an inner core and a shell layer, wherein the shell layer is wrapped around the outer core, the shell layer is a ceramicizable silicone rubber layer structure, and the inner core is a SiC nanowire with a continuous network structure;

[0008] The skeleton is a porous silicon carbide foam with a continuous network structure;

[0009] Among them, the core-shell structure is embedded in the skeleton structure in situ to form a double continuous network composite structure that is interlaced with each other.

[0010] As an improvement, it also includes a silicon carbide coating, which is attached to the surface of the skeleton by a chemical vapor deposition method.

[0011] As an improvement, the composite aerogel has an open porosity greater than 95% and a density of 10 kg / m 3 ~30kg / m 3 , compressive strength 0.03MPa~0.5MPa.

[0012] As an improvement, the shell layer has a thickness of 10-20 nm, the core has an amorphous structure, a diameter of 30-70 nm, and an aspect ratio of 2000-4000.

[0013] As an improvement, the shell layer includes at least one of organic silicone rubber, siloxane-containing silicone rubber, fluorinated modified silicone rubber and metal oxide modified silicone rubber.

[0014] As an improvement, the skeleton is a topological structure formed by three-dimensional repeated stacking of hollow polycyclic rings, and the thickness of the silicon carbide coating is no more than 15 nm.

[0015] As an improvement, the hollow polycyclic ring is at least one of a regular pentagon and a regular hexagon with a side length of 10 μm to 30 μm and a side diameter of 600 nm to 1200 nm.

[0016] As a specific embodiment of the present invention, a method for preparing a bicontinuous network composite aerogel with a large aspect ratio core-shell structure and in-situ embedded porous silicon carbide foam is also provided. The preparation method is to produce the above composite aerogel. The specific steps of the method include:

[0017] (1) Preparation of carbon foam matrix

[0018] The melamine foam is placed in a high-temperature furnace, evacuated and protected by inert gas, protective gas is introduced at a flow rate of 20 sccm to 80 sccm, the temperature is slowly raised to 800° C. to 1100° C., and the temperature is kept for 0.5 h to 2 h, and then cooled to obtain a carbon foam skeleton matrix;

[0019] (2) Preparation of silicon carbide coating

[0020] The substrate obtained in (1) is placed in a chemical vapor deposition device, an inert gas is introduced into the methyltrichlorosilane MTS solution, and then brought into the deposition device, and the gas is continuously ventilated until the valves on both sides of the deposition device are closed, and the temperature is slowly increased. After deposition for a period of time, the substrate is slowly cooled to room temperature to obtain a porous carbon foam skeleton structure covered with a silicon carbide coating;

[0021] (3) Pyrolysis treatment

[0022] The porous carbon foam skeleton structure coated with the silicon carbide coating obtained in (2) is placed in a high-temperature furnace, heated to 500° C. to 800° C. in an air atmosphere for 2 h to 4 h to obtain a porous silicon carbide foam skeleton;

[0023] (4) Nickel salt immersion treatment

[0024] The porous silicon carbide foam skeleton obtained in (3) is immersed in a nickel salt solution for 5 to 120 minutes, and then dried in an environment of 40° C. to 100° C. until the ethanol solvent is completely evaporated;

[0025] (5) Preparation of silicon carbide nanowires

[0026] The material obtained in (4) is placed in a vacuum furnace, and the temperature is slowly raised to 900°C to 1200°C at a flow rate of 30 sccm to 70 sccm of inert gas; then, after evacuation, H2 and MTS are introduced simultaneously, and the temperature is kept for 1h to 3h and then cooled to room temperature to obtain a large aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel;

[0027] (6) Silicone rubber filling and degassing

[0028] The high aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel obtained in (5) is placed in a vacuum device, a mixture of ceramicizable silicone rubber and solvent is pumped into the device, and degassing is performed at a certain temperature and a certain vacuum degree to obtain a high aspect ratio core-shell structure SiC@CSR nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel;

[0029] (7) Curing and molding

[0030] The composite aerogel obtained in (6) is cured at 80° C. to 200° C. for 6 h to 10 h to form a final composite aerogel.

[0031] As an improvement, in step (4), the nickel salt solution is a mixture of one or more of nickel nitrate, nickel chloride, nickel acetate or nickel sulfate, and the solvent is ethanol.

[0032] As an improvement, in step (6), the degassing temperature is 40°C to 80°C and the vacuum degree is 0.01MPa to 0.08MPa.

[0033] Beneficial effects: The present invention achieves synergistic optimization of the multifunctionality, energy absorption and high temperature resistance of the composite aerogel by precisely designing the mechanical distribution and coupling characteristics of nanowires, ceramic skeletons and porous structures. It has significant advantages in the regulation of sound waves, electromagnetic waves and light waves, as well as high-temperature anti-oxidation and anti-vibration. This makes it have broad application potential in aerospace, military protection, electronic equipment, building seismic isolation and other fields.

[0034] At the same time, the composite aerogel and preparation method proposed in the present invention have the following advantages compared with conventional ones:

[0035] (1) The present invention is lightweight and multifunctional, which is specifically embodied in the following aspects: a design scheme of combining multiple dielectric materials with multi-level pore structures is adopted. Based on the characteristics of high-transmittance silicone rubber, semiconductor-property silicon carbide nanowire electron transport and Young's modulus, it can form a coordinated response to mechanical waves, light waves and radar waves at a relatively low frequency (≤200Hz), as well as rapid thermal energy conversion and dissipation of energy in various wavebands, thereby realizing a logical design of multifunctional characteristics.

[0036] In addition, based on the hollow template and the homogenization of the composite aerogel by nanowires with a large aspect ratio and the effective multi-level segmentation, effective restrictions on gas heat conduction are formed, and higher thermal insulation performance can be achieved under lighter conditions.

[0037] (2) The excellent energy absorption and vibration resistance of the present invention are specifically embodied in the porous silicon carbide template's own homogeneous micron pores embedded with large aspect ratio nanowires and multi-level aperture and mechanical wave coupling unit design, which can achieve mechanical wave response in a wide frequency range (see the attached manual). Figure 6 shown).

[0038] Furthermore, the outer silicone rubber coating not only enhances the vibration resistance, but also provides multi-level energy buffering under the action of external force, so that the material can consume energy step by step under impacts and vibrations of different intensities, thereby reducing damage to the structure. It is particularly suitable for shock absorption, impact resistance and vibration resistance.

[0039] (3) The mild anti-oxidation capability of the present invention is specifically embodied in: the invention adopts a full ceramic structure, has excellent high temperature resistance, and can work stably for a long time in a high temperature environment.

[0040] In addition, the silicone rubber layer can be transformed into a ceramic phase at high temperatures, further enhancing the material's high temperature resistance and oxidation resistance, solving the temperature resistance problem of traditional carbon-based materials in high temperature oxidizing environments, and can have a longer service life in applications in high temperature and corrosive environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a flow chart for preparing the SiC@CSR nanowire-embedded porous silicon carbide foam composite aerogel of the present invention.

[0042] Figure 2 Schematic diagram of the structure of the SiC@CSR nanowire-embedded porous silicon carbide foam composite aerogel of the present invention.

[0043] Figure 3 It is a schematic diagram of the structure of a single SiC nanowire coated with a ceramicizable silicone rubber coating.

[0044] Figure 4 This is the microscopic morphology of the SiC embedded porous carbon foam material prepared in Example 2 of the present invention.

[0045] Figure 5 This is the statistical result of the SiC nanowires prepared in Example 2 of the present invention.

[0046] Figure 6 is the compressive strength of the composite aerogel prepared in Example 2 of the present invention.

[0047] Figure 7 is the reflection loss of the wave absorbing performance of the composite aerogel prepared in Example 3 of the present invention.

[0048] In the figure: 21. Core-shell structure SiC@CSR nanowire, 22. Porous silicon carbide foam skeleton, 31. SiC nanowire, 32. Ceramic silicone rubber coating. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention will be described clearly and completely below so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0050] The present invention provides a double continuous network composite aerogel with a large aspect ratio core-shell structure in-situ embedded with porous silicon carbide foam, comprising a core-shell structure and a skeleton; the core-shell structure comprises an inner core and a shell layer, wherein the shell layer is wrapped outside the inner core, the shell layer is a ceramic silicone rubber layer structure, and the inner core is a SiC nanowire with a continuous network structure;

[0051] The skeleton is a porous silicon carbide foam with a continuous network structure;

[0052] Among them, the core-shell structure is embedded in the skeleton structure in situ to form a composite structure of mutually interlaced double continuous networks.

[0053] In the present invention, on the one hand, by designing a continuous network structure of silicon carbide nanowires in the core-shell structure and a porous silicon carbide foam structure with a continuous network as the skeleton structure, a double continuous network composite structure is formed; on the other hand, by embedding the core-shell structure in situ on the skeleton, a chemical bond with strong binding force is formed, which is not easy to fall off, thereby achieving the seismic resistance and good energy absorption effect of the entire structure.

[0054] At the same time, the shell-core structure of the present invention uses a ceramic silicone rubber (Criticizable silicone rubber, CSR) layer as a shell layer and a silicon carbide nanowire as a core, that is, the SiC@CSR nanowire structure of the present invention, and the CSR nanowire is designed to have a large aspect ratio, with an aspect ratio of 2000 to 4000. The main effects of the large aspect ratio are as follows: 1. The large aspect ratio can maximize the free path of the nanowire under mechanical deformation conditions under the condition of the same fiber diameter, and increase the energy absorption value of the aerogel; in addition, the interpenetrating network of fibers with a large aspect ratio will cause the fibers to curl and entangle over a large range, forming more prestressed points, changing the response frequency of the fibers to sound waves, and forming effective acoustic regulation characteristics of the material in a wide frequency range; 2. The large aspect ratio fiber structure is conducive to more uniformly dividing the micron pores inside the SiC template, so that the reflection behavior of different signals (electromagnetic waves, sound waves and mechanical waves) after entering the material is improved, which is conducive to the coordinated optimization of different signals.

[0055] As a specific embodiment of the present invention, the skeleton is a structure formed by attaching a layer of silicon carbide coating to a carbon foam substrate by chemical vapor deposition and then foaming. Preferably, the skeleton is a topological structure formed by three-dimensional repeated stacking of hollow multi-rings, wherein the multi-rings are one of regular pentagons or regular hexagons with a side length of 10μm to 30μm and a side diameter of 600nm to 1200nm; the shell layer of the hollow multi-ring side, that is, the silicon carbide coating, is an amorphous SiC layer with a thickness not exceeding 15nm.

[0056] As a specific embodiment of the present invention, a core-shell structure has a shell layer of a ceramic silicone rubber CSR with a thickness of 10nm to 20nm, and an inner core of a SiC nanowire with a diameter of 30nm to 70nm.

[0057] Preferably, the ceramizable silicone rubber is a mixture of one or more of organic silicone rubber, siloxane-containing silicone rubber, fluorinated modified silicone rubber and metal oxide modified silicone rubber.

[0058] The following is a method for preparing a bicontinuous network composite aerogel having a large aspect ratio core-shell structure and in-situ embedded porous silicon carbide foam according to the present invention, described by way of specific examples.

[0059] 1. Preparation method (process as Figure 1 (shown)

[0060] Embodiment 1

[0061] (1) The melamine foam is placed in a high-temperature furnace, evacuated and protected by inert gas, protective gas is introduced at a flow rate of 20 sccm, the temperature is slowly raised to 800° C., and the temperature is maintained for 0.5 h and then cooled to obtain a carbon foam skeleton structure.

[0062] (2) Prepare porous silicon carbide coating by chemical vapor deposition technology. Place the carbon foam skeleton structure prepared in step (1) into a deposition device, pass an inert gas into the methyltrichlorosilane (MTS) solution at a flow rate of 20 sccm, and then bring it into the deposition device, and continue to ventilate for 5 minutes; then close the valves on both sides of the deposition device, slowly heat up to 1000°C, deposit for 5 minutes, and slowly cool to room temperature to obtain a silicon carbide coating-coated porous carbon foam skeleton structure.

[0063] (3) placing the silicon carbide coating-coated porous carbon foam skeleton structure obtained in step (2) in a high-temperature furnace, heating it to 500° C. in an air atmosphere for 2 h to obtain a porous silicon carbide foam skeleton.

[0064] (4) The porous silicon carbide foam skeleton was immersed in a nickel salt solution for 5 minutes and then dried in a 40° C. environment until the solvent was completely evaporated.

[0065] (5) Preparation of SiC nanowire filling phase. The material obtained in step (4) was placed in a vacuum furnace, and the temperature was slowly raised to 900°C at a flow rate of 30 sccm of inert gas; then, after evacuation, H2 and MTS were introduced simultaneously, and the temperature was kept for 1 hour and then cooled to room temperature to obtain a large aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel.

[0066] (6) Mixing the ceramic silicone rubber with the solvent to ensure that the viscosity of the mixed liquid is less than 4000 mPa·s and has high fluidity, and then placing the large aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel obtained in step (5) in a vacuum device, pumping in the mixed ceramic silicone rubber mixture, and degassing at 40° C. and a vacuum degree of 0.01 MPa to obtain a large aspect ratio core-shell structure SiC@CSR nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel.

[0067] (7) The composite aerogel obtained in step (6) was cured at 80°C for 6 hours to form a final composite aerogel. The composite aerogel had a porosity of 96.7% and a density of 12 kg / m 3 , reflection loss -60dB.

[0068] Embodiment 2

[0069] (1) The melamine foam is placed in a high-temperature furnace, evacuated and protected by inert gas, protective gas is introduced at a flow rate of 50 sccm, the temperature is slowly raised to 1000° C., and the temperature is maintained for 1 hour and then cooled to obtain a carbon foam skeleton structure.

[0070] (2) Prepare porous silicon carbide coating by chemical vapor deposition technology. Place the carbon foam skeleton structure prepared in step (1) into a deposition device, pass an inert gas into the methyltrichlorosilane (MTS) solution at a flow rate of 30 sccm, and then bring it into the deposition device, and continue to ventilate for 10 minutes; then close the valves on both sides of the deposition device, slowly heat up to 1100°C, deposit for 8 minutes, and slowly cool to room temperature to obtain a silicon carbide coating-coated porous carbon foam skeleton structure.

[0071] (3) placing the porous carbon foam skeleton structure coated with the silicon carbide coating obtained in step (2) in a high-temperature furnace, heating it to 700° C. in an air atmosphere for 3 hours to obtain a porous silicon carbide foam skeleton.

[0072] (4) The porous silicon carbide foam skeleton was immersed in a nickel salt solution for 60 minutes and then dried in an environment of 80° C. until the solvent was completely evaporated.

[0073] (5) Preparation of SiC nanowire filling phase. The material obtained in step (4) was placed in a vacuum furnace and slowly heated to 1050°C at a flow rate of 350 sccm of inert gas; then, after evacuation, H2 and MTS were introduced simultaneously, and the temperature was kept for 2 hours and then cooled to room temperature to obtain a large aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel.

[0074] (6) Mixing the ceramic silicone rubber with the solvent to ensure that the viscosity of the mixed liquid is less than 4000 mPa·s and has high fluidity, and then placing the large aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel obtained in step (5) in a vacuum device, pumping in the mixed ceramic silicone rubber mixture, and degassing at 60° C. and a vacuum degree of 0.05 MPa to obtain a large aspect ratio core-shell structure SiC@CSR nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel.

[0075] (7) The composite aerogel obtained in step (6) was cured at 140° C. for 8 h to form a final composite aerogel. The composite aerogel had a porosity of 97.4% and a density of 23 kg / m 3 , reflection loss -20dB.

[0076] Embodiment 3

[0077] (1) The melamine foam is placed in a high-temperature furnace, evacuated and protected by inert gas, protective gas is introduced at a flow rate of 80 sccm, the temperature is slowly raised to 1100° C., and the temperature is maintained for 2 hours and then cooled to obtain a carbon foam skeleton structure.

[0078] (2) Prepare porous silicon carbide coating by chemical vapor deposition technology. Place the carbon foam skeleton structure prepared in step (1) into a deposition device, pass an inert gas into the methyltrichlorosilane (MTS) solution at a flow rate of 50 sccm, and then bring it into the deposition device, and continue to ventilate for min; then close the valves on both sides of the deposition device, slowly heat up to 1300°C, deposit for 10 min, and slowly cool to room temperature to obtain a silicon carbide coating-coated porous carbon foam skeleton structure.

[0079] (3) Placing the porous carbon foam skeleton structure coated with the silicon carbide coating obtained in step (2) in a high-temperature furnace, heating it to 800° C. in an air atmosphere for 4 hours to obtain a porous silicon carbide foam skeleton.

[0080] (4) The porous silicon carbide foam skeleton is immersed in a nickel salt solution for 120 minutes and then dried in a 100° C. environment until the solvent is completely evaporated.

[0081] (5) Preparation of SiC nanowire filling phase. The material obtained in step (4) was placed in a vacuum furnace, and the temperature was slowly raised to 1200°C at a flow rate of 70 sccm of inert gas; then, after evacuation, H2 and MTS were introduced simultaneously, and the temperature was kept for 3 hours and then cooled to room temperature to obtain a large aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel.

[0082] (6) Mixing the ceramic silicone rubber with the solvent to ensure that the viscosity of the mixed liquid is less than 4000 mPa·s and has high fluidity, and then placing the large aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel obtained in step (5) in a vacuum device, pumping in the mixed ceramic silicone rubber mixture, and degassing at 80° C. and a vacuum degree of 0.08 MPa to obtain a large aspect ratio core-shell structure SiC@CSR nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel.

[0083] (7) The composite aerogel obtained in step (6) was cured at 200° C. for 10 hours to form a final composite aerogel. The composite aerogel had a porosity of 98.8% and a density of 30 kg / m 3 , reflection loss -70dB.

[0084] 2. Experimental Test

[0085] The performance test experiments were carried out on multiple groups of composite aerogels prepared in Examples 1 to 3.

[0086] 2.1 Micromorphology

[0087] See Figure 2-Figure 3It can be clearly seen that the composite aerogel structure includes a porous silicon carbide foam skeleton 22 with in-situ grown core-shell structure SiC@CSR nanowires 21 embedded therein. By performing SEM on the composite aerogel prepared in the present invention, such as a group of products in Example 2, it can be seen that Figure 4 As shown, it can be obtained that SiC nanowires with a large aspect ratio are in-situ embedded in a porous silicon carbide foam skeleton.

[0088] 2.2 Compressive strength test

[0089] Figure 5-Figure 6 , Figure 5 This is a statistical analysis of the diameters of SiC nanowires in Example 2. It can be seen that the average diameter of the nanowires is 64 nm. Figure 6 The product in Example 1 was subjected to a compression test. The compression performance was tested on a microcomputer-controlled universal testing machine (E43.104, MTS, China). The sample size was 10mm*10mm, the compression strain was 75%, and the compression stress was obtained by dividing the pressure obtained by the sensor by the sample area. It can be seen from the stress-strain curve that when the deformation is 50%, the compressive strength reaches 50kPa, and increases with the increase of the deformation. No destructive fracture occurred during the compression process, reflecting the structural stability of the composite aerogel.

[0090] 2.3 Wave absorption performance test

[0091] Figure 7 It is the reflection loss of the wave absorption performance of the composite aerogel prepared in Example 3. The electromagnetic parameters of the sample were tested using a vector network analyzer (Ceyear 3672B, China Electronics Cosine Instrument), and the implementation standard was GB / T 35679-2017. The sample was prepared by mixing the fiber and paraffin in a ratio of 4:6 to form concentric rings with an outer diameter of 7 mm and an inner diameter of 3.04 mm. The obtained electromagnetic parameters were obtained by origin mapping. It can be seen that it has excellent electromagnetic wave absorption performance.

[0092] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A bicontinuous network composite aerogel with a large aspect ratio core-shell structure and in-situ embedded porous silicon carbide foam, characterized in that: Including shell core structure and skeleton; The core-shell structure comprises an inner core and a shell layer, wherein the shell layer is wrapped around the outer core, the shell layer is a ceramicizable silicone rubber layer structure, and the inner core is a SiC nanowire with a continuous network structure; The skeleton is a porous silicon carbide foam with a continuous network structure; Among them, the core-shell structure is embedded in the skeleton structure in situ to form a double continuous network composite structure that is interlaced with each other.

2. According to claim 1, the bicontinuous network composite aerogel with a core-shell structure and in-situ embedded porous silicon carbide foam with a large aspect ratio, characterized in that: The skeleton is a structure formed by attaching a layer of silicon carbide coating on a carbon foam substrate by chemical vapor deposition and then performing foaming treatment.

3. The bicontinuous network composite aerogel with a core-shell structure and in-situ embedded porous silicon carbide foam with a large aspect ratio according to claim 1, characterized in that: The composite aerogel has an open porosity greater than 95% and a density of 10 kg / m 3 ~30kg / m 3 , compressive strength 0.03MPa~0.5MPa.

4. The bicontinuous network composite aerogel with a core-shell structure and in-situ embedded porous silicon carbide foam with a large aspect ratio according to claim 1, characterized in that: The shell layer has a thickness of 10 to 20 nm, the core is an amorphous structure with a diameter of 30 to 70 nm, and the aspect ratio of the core is 2000 to 4000.

5. The bicontinuous network composite aerogel with a core-shell structure and in-situ embedded porous silicon carbide foam with a large aspect ratio according to any one of claims 1 to 4, characterized in that: The shell layer includes at least one of organic silicone rubber, siloxane-containing silicone rubber, fluorinated modified silicone rubber and metal oxide modified silicone rubber.

6. The bicontinuous network composite aerogel with a core-shell structure and in-situ embedded porous silicon carbide foam of claim 1, characterized in that: The skeleton is a topological structure formed by three-dimensional repeated stacking of hollow polycyclic rings, and the thickness of the silicon carbide coating is no more than 15 nm.

7. The bicontinuous network composite aerogel with a core-shell structure and in-situ embedded porous silicon carbide foam of claim 5, characterized in that: The hollow polycyclic ring is at least one of a regular pentagon and a regular hexagon with a side length of 10 μm to 30 μm and a side diameter of 600 nm to 1200 nm.

8. The method for preparing a bicontinuous network composite aerogel with a large aspect ratio core-shell structure and in-situ embedded porous silicon carbide foam according to claim 1, characterized in that: The following steps are involved: (1) Preparation of carbon foam matrix The melamine foam is placed in a high-temperature furnace, evacuated and protected by inert gas, protective gas is introduced at a flow rate of 20 sccm to 80 sccm, the temperature is slowly raised to 800° C. to 1100° C., and the temperature is kept for 0.5 h to 2 h, and then cooled to obtain a carbon foam skeleton matrix; (2) Preparation of silicon carbide coating The substrate obtained in (1) is placed in a chemical vapor deposition device, an inert gas is introduced into the methyltrichlorosilane MTS solution, and then brought into the deposition device, and the gas is continuously ventilated until the valves on both sides of the deposition device are closed, and the temperature is slowly increased. After deposition for a period of time, the substrate is slowly cooled to room temperature to obtain a porous carbon foam skeleton structure covered with a silicon carbide coating; (3) Pyrolysis treatment The porous carbon foam skeleton structure coated with the silicon carbide coating obtained in (2) is placed in a high-temperature furnace, heated to 500° C. to 800° C. in an air atmosphere for 2 h to 4 h to obtain a porous silicon carbide foam skeleton; (4) Nickel salt immersion treatment The porous silicon carbide foam skeleton obtained in (3) is immersed in a nickel salt solution for 5 to 120 minutes, and then dried in an environment of 40° C. to 100° C. until the solvent ethanol is completely evaporated; (5) Preparation of silicon carbide nanowires The material obtained in (4) is placed in a vacuum furnace, and the temperature is slowly raised to 900°C to 1200°C at a flow rate of 30 sccm to 70 sccm of inert gas; then, after evacuation, H2 and MTS are introduced simultaneously, and the temperature is kept for 1h to 3h and then cooled to room temperature to obtain a large aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel; (6) Silicone rubber filling and degassing The high aspect ratio SiC nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel obtained in (5) is placed in a vacuum device, a mixture of ceramicizable silicone rubber and ethanol is pumped into the device, and the device is degassed at a certain temperature and a certain vacuum degree to obtain a high aspect ratio core-shell structure SiC@CSR nanowire embedded porous silicon carbide foam bicontinuous network composite aerogel; (7) Curing and molding The composite aerogel obtained in (6) is cured at 80° C. to 200° C. for 6 h to 10 h to form a final composite aerogel.

9. The method for preparing the bicontinuous network composite aerogel with a core-shell structure and in-situ embedded porous silicon carbide foam with a large aspect ratio according to claim 8, characterized in that: In step (4), the nickel salt solution is a mixture of one or more of nickel nitrate, nickel chloride, nickel acetate or nickel sulfate, and the solvent is ethanol.

10. The method for preparing the bicontinuous network composite aerogel with a core-shell structure and in-situ embedded porous silicon carbide foam with a large aspect ratio according to claim 8, characterized in that: In step (6), the degassing temperature is 40°C to 80°C and the vacuum degree is 0.01MPa to 0.08MPa.

Citation Information

Patent Citations

  • Carbon foam resin matrix composite base plate coated with silicon carbide coating and preparation method thereof

    CN109734478A

  • Silicone rubber composite material capable of being vitrified, and preparation method and application thereof

    CN113881233A

  • Efficient fireproof silicone rubber composite sleeve and preparation method thereof

    CN117511224A

  • A ceramic silicone rubber composite belt

    CN118572319B

  • Silicon carbide / hafnium carbide nanowire modified silicon carbide coating reinforced graphene honeycomb-based nano aerogel heat-insulating and wave-absorbing composite material

    CN114466580A

Cited By

  • Carbon-rich SiC-coated Si3N4 double-network aerogel and preparation method thereof

    CN121292980A

  • Wave-absorbing ceramic complex with shock-resistant cladding structure and preparation method of wave-absorbing ceramic complex

    CN122458398A